Impact of Early SARS-CoV-2 Antiviral Therapy on Disease Progression - De Vito, Andrea; Colpani, Agnese; Saderi, Laura; Puci, Mariangela; Zauli, Beatrice; Fiore, Vito; Fois, Marco; Meloni, Maria Chiara; Bitti, Alessandra; Di Castri, Cosimo; Maida, Ivana; Babudieri, Sergio; et al. (Viruses, 2022)
Since the start of the SARS-CoV-2 pandemic, several treatments have been proposed to prevent the progression of the disease. Currently, three antiviral (molnupiravir, nirmaltrevir/r, remdesivir) and two monoclonal antibodies (casirivimab/imdevimab and sotrovimab) are available in Italy. Therefore, we aimed to evaluate the presence of risk factors associated with disease progression. We conducted a retrospective cohort study, including all patients with a confirmed diagnosis of SARS-CoV-2 evaluated between 01/01/2022 ad 10/05/2022 by our Unit of Infectious Diseases in Sassari. We defined disease progression as the necessity of starting O2 therapy. According to AIFA (Italian Medicines Agency) indications, preventive treatment was prescribed in patients with recent symptoms onset (≤five days), no need for oxygen supplementation, and risk factors for disease progression. Subgroup differences in quantitative variables were evaluated using Student’s t-test. Pearson chi-square or Fisher’s exact tests were used to assess differences for qualitative variables. Multivariate logistic regression modelling was performed to determine factors associated with progression. A two-tailed p-value less than 0.05 was considered statistically significant. All statistical analyses were performed with STATA version 17 (StataCorp, College Station, TX, USA). We included 1145 people with SARS-CoV-2 diagnosis, of which 336 (29.3%) developed severe disease with oxygen supplementation. In multivariate logistic regression analysis, age, dementia, haematologic tumors, heart failure, dyspnoea or fever at first evaluation, having ground glass opacities or consolidation at the first CT scan, and bacteria coinfection were associated with an increased risk of disease progression. Vaccination (at least two doses) and early treatment with antiviral or monoclonal antibodies were associated with a lower risk of disease progression. In conclusion, our study showed that vaccination and early treatment with antiviral and/or monoclonal antibodies significantly reduce the risk of disease progression.